2024
DOI: 10.1021/acs.est.3c10898
|View full text |Cite
|
Sign up to set email alerts
|

Were Persulfate-Based Advanced Oxidation Processes Really Understood? Basic Concepts, Cognitive Biases, and Experimental Details

Xiaonan Hu,
Mingshan Zhu

Abstract: Persulfate (PS)-based advanced oxidation processes (AOPs) for pollutant removal have attracted extensive interest, but some controversies about the identification of reactive species were usually observed. This critical review aims to comprehensively introduce basic concepts and rectify cognitive biases and appeals to pay more attention to experimental details in PS-AOPs, so as to accurately explore reaction mechanisms. The review scientifically summarizes the character, generation, and identification of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(1 citation statement)
references
References 512 publications
(1,456 reference statements)
0
1
0
Order By: Relevance
“…However, the characteristic signal of 1 O 2 was not detected by ESR. The literature also reported that FFA could inhibit the electron transfer mechanism because the oxidation potential of FFA was weaker than the potential of catalyst/oxidant complex. , Thus, 1 O 2 was not generated in the system, and the electron transfer mechanism (ETP) might dominate the catalytic removal of the SAs. To further verify this hypothesis, a divided cell setup was employed to observe the current and voltage changes during the electron transfer process (Figure S34).…”
Section: Resultsmentioning
confidence: 99%
“…However, the characteristic signal of 1 O 2 was not detected by ESR. The literature also reported that FFA could inhibit the electron transfer mechanism because the oxidation potential of FFA was weaker than the potential of catalyst/oxidant complex. , Thus, 1 O 2 was not generated in the system, and the electron transfer mechanism (ETP) might dominate the catalytic removal of the SAs. To further verify this hypothesis, a divided cell setup was employed to observe the current and voltage changes during the electron transfer process (Figure S34).…”
Section: Resultsmentioning
confidence: 99%